2011
DOI: 10.2527/jas.2010-3722
|View full text |Cite
|
Sign up to set email alerts
|

COMPANION ANIMALS SYMPOSIUM: Environmental enrichment for companion, exotic, and laboratory animals1

Abstract: Animal scientists have an extraordinary burden to promote the health and well-being of all animals in their care. Promoting species- or breed-appropriate behaviors through proper training and enrichment, regardless of animal housing, should be a paramount concern for all animal scientists working with exotic animals, laboratory animals, shelter animals, or privately owned pet animals. Developing ideal training and enrichment programs for any species begins with understanding basic behavior patterns and emotion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 83 publications
0
6
0
Order By: Relevance
“…Beyond the financial advantages of the MA system, there are animal welfare issues that must be considered. Spatial restriction is one of the factors that generates more stress [ 22 , 23 , 24 ], contributing to a decrease in animal welfare in kennels [ 24 ]. Numerous studies have already highlighted that dogs housed in kennel facilities for long periods of time experience suboptimal living conditions [ 22 , 25 , 26 , 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Beyond the financial advantages of the MA system, there are animal welfare issues that must be considered. Spatial restriction is one of the factors that generates more stress [ 22 , 23 , 24 ], contributing to a decrease in animal welfare in kennels [ 24 ]. Numerous studies have already highlighted that dogs housed in kennel facilities for long periods of time experience suboptimal living conditions [ 22 , 25 , 26 , 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…The premise is that enrichment feeding more closely matches the way that pets would eat naturally and will thus have positive welfare outcomes. 9,10 Stray dogs are scavengers, eating several small meals a day, which should be mimicked if aiming to encourage natural behaviours. 11 It has been suggested that some level of cognitive challenge and problem solving to access food can have a positive effect on mood.…”
Section: Introductionmentioning
confidence: 99%
“…Enrichment feeding is advocated for cats and dogs in both kennels and home environments 4–8 ; however, empirical research to support this is scarce. The premise is that enrichment feeding more closely matches the way that pets would eat naturally and will thus have positive welfare outcomes 9,10 . Stray dogs are scavengers, eating several small meals a day, which should be mimicked if aiming to encourage natural behaviours 11 .…”
Section: Introductionmentioning
confidence: 99%
“…It is well documented that captive animals experience stress (eg, Beerda and others 2000 , Markowitz and Woodworth 1978 , Morris and others 2011 ), and a goal of optimal welfare should be to minimise stress. As we work towards this goal by changing the social or physical environment, the effect of the change should be reflected by the animal; it is important therefore to establish meaningful, measurable outcomes of any inputs designed to increase welfare ( Maple and Perdue 2013 ).…”
Section: Introductionmentioning
confidence: 99%